A Few Good Men: It's Not Easy Recruiting Male Hospice Palliative Care Volunteers. (December 2018) - Claxton-Oldfield, Stephen; McCaffrey-Noviss, Willa; Hicks, Robert
Two studies were conducted to explore how to engage male volunteers in hospice palliative care. Four male hospice palliative care volunteers were interviewed in study 1. The men agreed that a direct approach is best when it comes to recruiting male volunteers, especially a personal story or testimonial. Two different volunteer position descriptions were created for study 2: one description was similar to what might appear on a community-based hospice palliative care program's web site or in a newspaper ad looking for visiting hospice palliative care volunteers; the other description was in the form of a personal testimonial ostensibly written by a male hospice palliative care volunteer describing his role through examples of interactions he has had with patients and patients' family members. Twenty-five males responded to each description. Both of the descriptions generated low and nonsignificantly different levels of interest in becoming a hospice palliative care volunteer. Believing this work to be too emotionally demanding and not having enough time for volunteering were the two most commonly given reasons for not wanting to become a hospice palliative care volunteer. Suggestions for future recruitment efforts are discussed.